Analisis Kesalahan Berbahasa Tataran Morfologi dalam Tajuk Rencana Surat Kabar Kompas - Alber, Alber; Febria, Rhani; Fatmalia, Riana (GERAM, 2018)
Language error analysis is a study about disorder of language use based on grammatical rules. This research is aimed to analyze and interpret morphological errors in Kompas Editorials. It works on perspective content analysis method by applying documentation and hermeneutic techniques. Data collection techniques applied in this research by reading, recording, and grouping the data based on morphological categories. This research reveals that inappropriate affix uses, affix omission in particular use of prefix, suffix, and confix. To conclude, the use of official, accurate, acceptable Indonesian language should be concerned in writing the news.